Social Resilience and Adaptive Strategies of Female-Headed Households in Indonesia: A Strength-Based Social Work Perspective - Tuti Kartika; Bambang Rustanto; Aryohaji Istyawan; Rajendra Panggita Vasthu (Asean Social Work Journal, 2026)
Female-headed households (FHHs), locally referred to as Perempuan Kepala Keluarga (PEKKA), represent a socially vulnerable group facing multiple and intersecting challenges in simultaneously managing productive and reproductive roles. Within a persistently patriarchal social context, FHHs often experience limited access to economic resources, employment opportunities, and social support. Despite these constraints, many demonstrate strong adaptive capacities that enable them to sustain household livelihoods. This study aims to analyze the adaptive strategies developed by female-headed households in Garut, Indonesia, and to examine how these strategies contribute to the formation of social and economic resilience from a strength-based social work perspective, with relevance to the ASEAN region. This study employed a qualitative descriptive approach using in-depth interviews, participant observation, focus group discussions, and document analysis. Data were collected from five key informants and seventeen participants from PEKKA groups. Thematic analysis following Braun and Clarke was applied to identify patterns of resilience across the dimensions of power within, power with, and power to. The findings indicate that FHHs develop adaptive strategies through role prioritization, reliance on kinship networks, livelihood diversification, and engagement with community and government programs. Social resilience emerges not merely from external interventions but from internal strengths and collective solidarity.